A simplified statistic-based procedure for gas dispersion prediction of fixed offshore platform - Shi, Jihao; Li, J.; Zhu, Y.; Hao, Hong; Chen, G.; Xie, B. (Elsevier, 2018)
© 2017 In explosion risk analysis, Frozen Cloud Approach (FCA) and Dimensionless Response Surface Method (DRSM) are both commonly used to achieve a balance between simulation workloads and accurate results. However, the drawbacks of these two approaches are obvious. FCA is not reliable for risk study of fuel-dominated regions. Whereas DRSM usually couples the dimensionless parameters and generates a large numbers of correlations to predict the flammable cloud size, which brings a heavy computation burden for engineers. Therefore, this paper aims to propose a simplified procedure which can quickly and accurately provide a large number of non-simulation data based on limited CFD simulation data. Full Factorial Design of Experiment (FFDOE) based RSM is adopted. Codification is applied to couple all the dimensional parameters into a single correlation. Automatically Selected Model Technology (ASMT) is used to easily determine the suitable structure of correlation. Compared to the conventional procedures, the simplified procedure is proven to be more robust. For subsequent Explosion risk analyses (ERAs) in the fuel-dominated regions, the simplified procedure becomes a superior alternative.